O'Reilly Design Conference 2016, San Francisco, California : video compilation (O'Reilly Media, 2016)
"With this video, you can explore an array of essential topics delivered by more than 70 design innovators. The O'Reilly Design Conference revolved around three primary themes: the new design fundamentals; design in business; and designing for greater good. Presentations from design leaders such as Robert Bruner (Ammunition), Margaret Stewart (Facebook), and Tony Fadell (Nest) will stoke your passion, enhance your skills, and expand your knowledge of design's many aspects, from the practical to the philosophical. The O'Reilly Design Conference video compilation includes nearly every session in these areas: The new fundamentals: Take your skills to the next level with presentations on industrial design, information architecture, user research, prototyping for connected devices, designing secure experiences, and UX for the IoT. Design and business: Master the topics that enable you to play a crucial role in your organization's success--selling your design concepts, designing for conversion and performance, leadership, branding, metrics, and analytics. Design for a greater good: Learn how design can have positive social impact in such areas as education, government, healthcare, sustainability, and more, for the good of the global community. Design doesn't stand still. Neither should you. This video will prepare you to shape the future today."--Resource description page.